Health and social determinant protectors in the university environment - Jorge Coronel Carbo; Nathaly Marzo Páez (Centro Provincial de Información de Ciencias Médicas, 2018)
It is a comment on health and social determinants protectors in the higher education institutions from Latin America; as well as on the risk factors in this environment, at the same time, some experiences are mentioned in relation to health promoter universities in Latin America and the Caribbean, which represent a great challenge in the present historical context.